The last emperor - Behr, Edward (Bantam Books New York, 1987)
Tells the story of Pu Yi, who became Emperor of China at age three, was made puppet emperor of Manchuria by the Japanese, was captured by the Russians, and was reeducated in Red Chinese prison This is the historical biography of the elusive man who once reigned over nearly half the world's population
Biography. (Movie made based on this book.)
Keywords: Puyi; Kings and rulers -- Biography -- China